The Evolution of Additive Manufacturing in Academia - Botelho, Guilherme Ferreira (2022)
This study aims to relate the segment of additive manufacturing to academia and the impact on the development of new adjustment techniques for a better use of the full capacity of the 3D printer in the development of new products. The main idea of ??additive manufacturing (3D printing) in the academic environment is to facilitate students' understanding of visualizing their prototypes once idealized in three-dimensional models on a printed piece so as to facilitate their understanding and adjustments of this product with greater ease. With the arrival of 3D printing at universities, many students will have their first contact with their project leaving the paper and becoming a finished product through a few steps. Regarding the time of the idealized project, its preparation in a ready-made piece, following all safety standards, the student can test different densities and adjustment to obtain a finished piece with density and mechanical resistance, he will be able to see in real time how his project will behave when subjected to field test. This type of tool empowers people to develop small prototypes in their homes through programs such as CAD (Computer Aided Design), where you can project and visualize an object.